2015
DOI: 10.1002/jmr.2512
|View full text |Cite
|
Sign up to set email alerts
|

Purification and molecular characterization of a novel mannose‐specific lectin from Dioclea reflexa hook seeds with inflammatory activity

Abstract: A novel lectin present in Dioclea reflexa seeds (DrfL) was discovered and described in this study. DrfL was purified in a single step by affinity chromatography in a Sephadex G-50 column. The lectin strongly agglutinated rabbit erythrocytes and was inhibited by α-methyl-D-mannoside, D-mannose, and D-glucose. The hemagglutinating activity of DrfL is optimum at pH 5.0-7.0, stable up to 50 °C, and dependent on divalent cations. Similar to other lectins of the subtribe Diocleinae, the analysis by mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Other lectins of the same botanical family show maximum activity at similar temperatures, such as the Collaea speciosa lectin isolated by Oliveira et al (2021) and the lectin isolated by Alves et al (2015) from seeds of Clathrotropis nitida, which showed low hemagglutinating activity at 100 ºC. Total dependence of CiL on divalent ions, as noted above, closely resembled the findings of Pinto-Junior et al (2016) who isolated a metal-dependent lectin from the seeds of Dioclea reflexa. These data diverge from those of other lectins, such as Dioclea lasiophylla (lectin II -specific lactose) (Cavada et al 2020) and Canavalia virosa (Osterne et al 2014).…”
Section: Physicochemical Characterizationsupporting
confidence: 72%
“…Other lectins of the same botanical family show maximum activity at similar temperatures, such as the Collaea speciosa lectin isolated by Oliveira et al (2021) and the lectin isolated by Alves et al (2015) from seeds of Clathrotropis nitida, which showed low hemagglutinating activity at 100 ºC. Total dependence of CiL on divalent ions, as noted above, closely resembled the findings of Pinto-Junior et al (2016) who isolated a metal-dependent lectin from the seeds of Dioclea reflexa. These data diverge from those of other lectins, such as Dioclea lasiophylla (lectin II -specific lactose) (Cavada et al 2020) and Canavalia virosa (Osterne et al 2014).…”
Section: Physicochemical Characterizationsupporting
confidence: 72%
“…The lethality test using Artemia is a simple preliminary assay to determine toxicity of CsL against cells [17,62,63,64]. When toxicity of CsL for Artemia was examined using lectin concentrations ranging between 3.125 and 200 μg/mL, it was found that this lectin is innocuous to Artemia sp.…”
Section: Toxicity Of Csl Against Artemia Naupliimentioning
confidence: 99%
“…Edematogenic activity has been studied in ConA [31], ConGF [35], ConBr [29], Canavalia gladiata lectin (CGL) [29], C. maritima lectin (ConM) [29], C. virosa lectin (ConV) [36], C. oxyphylla lectin (CoxyL) [19], C. villosa lectin (CvilL) [20], Dioclea rostrata lectin (DRL) [37], D. wilsonii lectin (DWL) [38,39], D. virgata lectin (DvirL) [40], D. lasiophylla lectin (DlyL) [41], D. reflexa lectin (DrfL) [41] and Cymbosema roseum lectin (CRL1) [42] (Table 1). Anti-inflammatory effect has been studied in ConGF [43], DvirL [33], CRL1 [42], D. guianensis lectin (DguiL), D. violacea lectin (DVL) and Cratylia floribunda lectin (CFL) [28].…”
Section: Biological Activities Of Cona-like Lectinsmentioning
confidence: 99%